(untitled) (International Journal of Engineering and Computer Science, 2017)
The World Wide Web (WWW) allows the people to share the information (data) from the large database repositories globally. In order to manage this data efficiently, we need to use specialized technologies to improve the user experience. This survey paper superficially explains the various web technologies such as HTML5 - Multimedia, Intelligent Semantic Web Search Engine, Web Data Mining, Distributed/Grid Computing and Image Processing.